A historical review of high heat flux cooling techniques - Ji Hwan Lim; Seung-Hwan Yu (Nuclear Engineering and Technology, 2025)
This review provides a comprehensive historical analysis of high heat flux cooling techniques critical for advanced applications in nuclear energy, aerospace propulsion, and high-performance electronics. We trace the evolution of cooling strategies from early nucleate boiling experiments to recent innovations such as swirl flow devices, Hypervapotron channels, screw tubes, and porous coatings. By synthesizing experimental results and theoretical models, we identify significant enhancements in critical heat flux (CHF) and heat transfer coefficients, with swirl flow techniques offering improvements of 50–100 % over smooth channels and Hypervapotron systems achieving CHF levels up to 30 MW/m2 under optimal conditions. Our review also highlights that while individual cooling methods exhibit unique performance benefits, an integrated hybrid approach holds promise for future high heat flux cooling systems. However, the translation from laboratory-scale success to practical, industrial-scale applications presents challenges, particularly in system complexity, maintenance, and cost analysis. We conclude that future research must bridge these gaps through interdisciplinary strategies, robust cost-analysis frameworks, and optimization studies. This balanced evaluation underscores both the technical achievements and the practical hurdles that define the current state and future potential of high heat flux cooling technologies.